2018
DOI: 10.3892/ijo.2018.4348
|View full text |Cite
|
Sign up to set email alerts
|

KIFC1, a novel potential prognostic factor and therapeutic target in hepatocellular carcinoma

Abstract: Kinesin family member C1 (KIFC1, also known as HSET) is a minus end-directed motor protein, which is critical in centrosome clustering. The present study investigated the expression of KIFC1 in paired hepatocellular carcinoma (HCC) tissues and adjacent non-cancerous tissues from 91 patients by immunohistochemical analysis; clinical data were concomitantly collected. KIFC1 was expressed at high levels in HCC tissues, compared with that in peritumoral tissues (54.9 vs. 14.3%; P<0.01), and its expression correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Several studies have shown that KIFC1 is associated with an apoptosis pathway [24,25]. We used RNA interference targeting KIFC1 in DU145-DR and C4-2-DR cells and confirmed the efficiency of KIFC1 knockdown by Western blotting ( Figure 3A).…”
Section: Inhibition Of Kifc1 Induces Apoptosis Pathway and Reverses Dsupporting
confidence: 60%
“…Several studies have shown that KIFC1 is associated with an apoptosis pathway [24,25]. We used RNA interference targeting KIFC1 in DU145-DR and C4-2-DR cells and confirmed the efficiency of KIFC1 knockdown by Western blotting ( Figure 3A).…”
Section: Inhibition Of Kifc1 Induces Apoptosis Pathway and Reverses Dsupporting
confidence: 60%
“…Various cancers also have increased Ran expression and enhanced RanGTP gradients due to increased DNA content (Hasegawa et al, 2013; Sheng et al, 2018; Xia et al, 2008). Some cancers also have increased HSET expression, which often correlates with metastasis and poor prognosis (Fu et al, 2018; Liu et al, 2016; Pannu et al, 2015; Patel et al, 2018). We propose that in cancer cells with increased HSET expression, the enhanced RanGTP gradients from higher DNA content promote HSET localization to the spindle, with a bias to the spindle poles that facilitates centrosome clustering by increased HSET-mediated cross-linking and sliding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KIFC1 is a minus end‐directed motor protein that is known for centrosome clustering in cancer cells . KIFC1 has been reported as a potential prognostic factor and therapeutic target in HCC, and a target protein of miR‐338‐3p in renal cell carcinoma . We then investigated expression of PKM2 and KIFC1 in HCC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%